PROLAPSE IN LAYING HENS: ITS PATHOPHYSIOLOGY AND MANAGEMENT : A REVIEW (Indian Journal of Animal Production and Management, 2014)
The egg industries have undergone significant transformation over the last four decades and it seems that this will persist, even though at a somewhat reduced rate, over the next 10 to 20 years. Because of advances in genetic selection, management and nutrition, the modern-day commercial layers have fast growth rates, high feed conversion ratios and metabolic rates. Layer production is undergoing change, in terms of potential for egg processing and more recently the start of major international trade in eggs. Despite such tremendous developments in layer nutrition and management some recurrent disorders are always present with some degree for most poultry species. Prolapse is one of such common disorders which invariably results in some economic loss each year. Prolapse in laying birds is the eversion of the oviduct and rectal organs through the vent to the extent that the organs don’t retract. The condition perpetually results in death even if the prolapse is discovered and the organs replaced in position. Not only nutrition, but also several other factors like hormonal disturbances, managmental errors, Pathological factors and many moreare responsible for incidence of this disorder.Therefore, a comprehensive understanding of different causes and remedies of prolapse in laying hens is necessary to take appropriate and effective preventive measures, which is to ensure better economic profitability.
Keywords: Layers; prolapse; oviduct; nutrition; management; cannibalism